If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3Q + -18 = 4Q + 14 + 10 Reorder the terms: -18 + 3Q = 4Q + 14 + 10 Reorder the terms: -18 + 3Q = 14 + 10 + 4Q Combine like terms: 14 + 10 = 24 -18 + 3Q = 24 + 4Q Solving -18 + 3Q = 24 + 4Q Solving for variable 'Q'. Move all terms containing Q to the left, all other terms to the right. Add '-4Q' to each side of the equation. -18 + 3Q + -4Q = 24 + 4Q + -4Q Combine like terms: 3Q + -4Q = -1Q -18 + -1Q = 24 + 4Q + -4Q Combine like terms: 4Q + -4Q = 0 -18 + -1Q = 24 + 0 -18 + -1Q = 24 Add '18' to each side of the equation. -18 + 18 + -1Q = 24 + 18 Combine like terms: -18 + 18 = 0 0 + -1Q = 24 + 18 -1Q = 24 + 18 Combine like terms: 24 + 18 = 42 -1Q = 42 Divide each side by '-1'. Q = -42 Simplifying Q = -42
| x-6(8x+6)=5-47x | | 4X+6=7-3 | | -2/3*4=x | | 7p-5(p-q)-p= | | -2/3*4= | | log(8x+11)=2 | | 2x+3=3x+20 | | 7x+2(x-5)=4 | | 5X+6+4X=3-6 | | 10(x+2)-4(2x+1)=2(x+6) | | E^9x=5.9 | | F(x)=-x^2+8x+7 | | 9n+2n-5=-60 | | 8(a+2)=72 | | F(x)=-x^2-6x+5 | | 3x-4+5x+20=180 | | 3x-4+5x+20=360 | | 5=log(x+1) | | 8+5(x-7)=8-4(x-8) | | 5X-7X+X=4-2X | | 5e+2.5=2.5-7.5c | | -5.5+3.5(1-9.5k)=25.5 | | 0.24x+3.8x=-2.02 | | 8+5x-35x=8-4x-32 | | 4(2b-3x)=7b+5x | | 8+5x-35x=8-4x+32 | | 8x-17b=7x | | n=2/4*7/8 | | 7+3x=-5x+13 | | 12x-(x+3)=30 | | 4(2x-3b)=7x+5b | | 12x-(x+3)=4 |